Selective ATP competitive leads of CDK4: Discovery by 3D-QSAR pharmacophore mapping and molecular docking approach. (December 2017) - Rondla, Rohini; PadmaRao, Lavanya Souda; Ramatenki, Vishwanath; Haredi-Abdel-Monsef, Aboubakr; Potlapally, Sarita Rajender; Vuruputuri, Uma
Graphical abstract: Highlights: Selective ATP Competitive Leads of CDK4 are discovered. Virtual shortcut of the combined 3D-QSAR pharmacophore mapping and molecular docking is applied. The known CDK4 inhibitors and leads showed a similar trend of binding interactions. The leads showed high dock score, good predicted activity & scaffold diversity. A key feature of acceptable ADME profile is noted for the leads. Abstract: The discovery of ATP competitive CDK4 inhibitors is an on-going challenging task in cancer therapy. Here, an attempt has been made to develop new leads targeting ATP binding site of CDK4 by applying 3D-QSAR pharmacophore mapping and molecular docking methods The outcome of 6 leads offers a significant contribution for selective CDK4 inhibition, since they show potential binding interactions with Val 96, Arg 101, and Glu 144 residues of CDK4, that are unique and from other kinases. It is worth noting that there is a striking similarity in binding interactions of the leads and known CDK4 inhibitors, namely Abemaciclib, Palbociclib and Ribociclib. Further key features, including high dock score value, good predicted activity, scaffold diversity, and the acceptable ADME profile of leads, provide a great opportunity for the development of highly potent and selective ATP competitive inhibitors of CDK4.